2021
DOI: 10.1007/s11696-021-01981-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene modified graphene for C60/C70 fullerenes capture and construction of energy storage materials

Abstract: Graphene functionalized with dianthracene malonate was synthesized and used subsequently for construction of covalently bound graphene-fullerene hybrid nanomaterials. For this purpose, novel approach of Diels–Alder reaction of C60/C70 fullerene cores with anthracene moieties previously introduced onto graphene surface was successfully employed. Structure and composition of obtained graphene and its derivatives were characterized using scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…First of all, small aggregates on the surface of graphene flakes can be seen in the case of G-BN6, G-BN7 and G-BN8. A similar structure was previously reported by our group for other fullerene-graphene hybrid nanomaterials [23]. However, in the present work, no noticeable difference in the size of fullerene aggregates present on graphene surface was observed, which allows the conclusion that investigated fullerene derivatives reveal similar tendency to aggregation.…”
Section: Surface Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…First of all, small aggregates on the surface of graphene flakes can be seen in the case of G-BN6, G-BN7 and G-BN8. A similar structure was previously reported by our group for other fullerene-graphene hybrid nanomaterials [23]. However, in the present work, no noticeable difference in the size of fullerene aggregates present on graphene surface was observed, which allows the conclusion that investigated fullerene derivatives reveal similar tendency to aggregation.…”
Section: Surface Analysissupporting
confidence: 92%
“…A similar route was also presented Zhang et al, where a fullerene derivative covalently bound to the surface of graphite oxide facilitated its exfoliation to single graphene sheets and prevented its later re-stacking [22]. In addition, our group has recently reported synthesis of graphene covalently modified with Diels-Alder adducts of fullerenes and anthracene, designed for construction of supercapacitor electrodes [23].…”
Section: Introductionmentioning
confidence: 60%
“…Piotrowski et al has recently reported synthesis of graphene covalently modified with Diels‐Alder adducts of fullerenes and anthracene, designed for construction of supercapacitor electrodes. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Piotrowski et al has recently reported synthesis of graphene covalently modified with Diels-Alder adducts of fullerenes and anthracene, designed for construction of supercapacitor electrodes. [16] It is pertaining to mention here that the uniform dispersion of nanoparticles into the conducting polymers matrix is an essential requirement to produce synergistic effect in the properties of "hybrid conducting nanocomposites." Significant enhancements in energy storage properties are thus observed during their device applications.…”
mentioning
confidence: 99%